RNF4 regulates DNA double-strand break repair in a cell cycle-dependent manner. Issue 6 (18th March 2016) - Kuo, Ching-Ying; Li, Xu; Stark, Jeremy M.; Shih, Hsiu-Ming; Ann, David K.
Abstract: Both RNF4 and KAP1 play critical roles in the response to DNA double-strand breaks (DSBs), but the functional interplay of RNF4 and KAP1 in regulating DNA damage response remains unclear. We have previously demonstrated the recruitment and degradation of KAP1 by RNF4 require the phosphorylation of Ser824 (pS824) and SUMOylation of KAP1. In this report, we show the retention of DSB-induced pS824-KAP1 foci and RNF4 abundance are inversely correlated as cell cycle progresses. Following irradiation, pS824-KAP1 foci predominantly appear in the cyclin A (-) cells, whereas RNF4 level is suppressed in the G0-/G1-phases and then accumulates during S-/G2-phases. Notably, 53BP1 foci, but not BRCA1 foci, co-exist with pS824-KAP1 foci. Depletion of KAP1 yields opposite effect on the dynamics of 53BP1 and BRCA1 loading, favoring homologous recombination repair. In addition, we identify p97 is present in the RNF4-KAP1 interacting complex and the inhibition of p97 renders MCF7 breast cancer cells relatively more sensitive to DNA damage. Collectively, these findings suggest that combined effect of dynamic recruitment of RNF4 to KAP1 regulates the relative occupancy of 53BP1 and BRCA1 at DSB sites to direct DSB repair in a cell cycle-dependent manner.